Facilitating Social Play for Children with PDDs: Effects of Paired Robotic Devices - Matsuda, Soichiro; Nunez, Eleuda; Hirokawa, Masakazu; Yamamoto, Junichi; Suzuki, Kenji (Frontiers in Psychology, 2017)
Interacting with toys and other people is fundamental for developing social communication skills. However, children with autism spectrum disorder (ASD) are characterized by having a significant impairment in social interaction, and often, this leads to a deficit in play skills. For this reason, methods of teaching play skills to young children with ASD have been well documented. Although previous studies have examined a variety of instructional strategies for teaching skills, few studies have evaluated the potential of using robotic devices. The purpose of the present study is to examine the effects of feedback made by colored lights and vibration via paired robotic devices, COLOLO, in social play with children with ASD. COLOLO is a system of paired spherical devices covered with soft fabric. All participants in this study were recruited as volunteers through the Department of Psychology at Keio University. The pilot study included three participants diagnosed with PDDs (5- to 6-year-old boys), and compared the conditions with and without automatic feedback from the devices (colored lights and vibration). The results indicated that the participants in the condition that included feedback from the devices had an increased number of manipulations of the toy and increased number of times looking at the therapist’s toy. In the experiment, a systematic replication of the pilot study was performed with three other participants diagnosed with PDDs (3- to 6-year-old boys), using an A-B-A-B design. Again, the results showed that in the condition with colored lights and vibration, the children increased their manipulations of the toy as well as looking at the therapist’s toy. These findings are discussed in terms of the potential of paired robotic devices as a method to facilitate social play for children with ASD.